The Role of Credit Unions in Realizing the Strength of the Community Economy and the Resilience of HR: A Systematic Literature Review - Wahyono Agustinus, Jati (Journal Business Inovation, Accounting and Management, 2025)
Changing the public's mindset is crucial for developing the nation's superior human resources, including financial literacy. Public trust in financial institutions is a key factor in people's financial borrowing/investment. The phenomenon of online loans (Pinjol) since Covid-19 is quite worrying. Several studies have examined both positive and negative aspects. A gap exists in the public's interest in online loans (Pinjol) alongside other microfinance (MF) options. The second gap is low financial literacy in the community. This gap is addressed by the novel concept of the MF Credit Union (CU), which mandates financial literacy for prospective members. The role of CU in shaping the resilience of superior human resources is to create an understanding of literacy. The role of CU is not only savings and loans, but also community empowerment with a cultural approach, which is a distinctive feature of CU compared to other MFs. The research method is a Systematic Literature Review (LSR). LSR has 5 stages: reviewing, classifying, and systematically reviewing journals. References to 20 journals from 2020 to 2024. Research results: the role of MF for families/communities: 50%. MF maximizes its benefits for member solidarity: 50%, MF overcomes family finances in the global crisis: 50%, empowering developing country communities: 65%. Non-financial assistance (training, human resource development, entrepreneurship: 15%). Locus in Indonesia, Ghana, Africa, India, Vietnam. Conclusion: CU as MF plays a role in empowering the community's economy, especially the underprivileged, CU has a special financial literacy to change and shape the community's mindset in financial management so as to create superior human resource resilience.